The linguocultural semantics of the anthroponyms and toponyms in G. Martin’s novel A Game of Thrones and the peculiarities of their translation into Ukrainain - Бобро, Марія Павлівна; Присяжнюк, Людмила Романівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2021)
The article analyses the linguocultural features of the anthroponyms and toponyms in fiction and their translation into Ukrainian (linguocultural factor taken into account) basing on G. Martin’s novel A Game of Thrones. The main differences between fiction onyms and real life onyms existing in language are defined. Fiction onyms are influenced by such factors as the cultural and social code, historical information, fiction space, the author’s attitude to this or that phenomenon. It is established that in the analysed novel, the characters’ names contain information about the status and place of living of their owners: the names of those who live in the North are based on old English, Scottish and Welsh names, the wildings get Scandinavian ones, those who live in the South get variants of Roman, Greek and Arabic names. The author often makes speaking names and allusions to real historic personalities. It is pointed out that the world in which the characters of the novel exist has a medieval English colouring, so the characters’ names often look like real names of that period or are their derivatives. Complex toponyms often contain parts of words that can be found among the toponyms of Great Britain and carry certain historic information. A conclusion is drawn about the expressive linguocultural features of the proper names of the novel by G. Martin A game of Thrones which reflect the nationally specific cultural and historic information. Choosing translation means in each case is up to the translator who has to consider the linguocultural factor too, as the translation of fiction onyms is much more difficult than the translation of real proper names. In certain cases, the translation can be called more or less successful but there is no single strategy for rendering authorial proper names that carry semantic and cultural information.